In praise of other model organisms - Warren, Graham (J Cell Biol, 2015)
The early cell biological literature is the resting place of false starts and lost opportunities. Though replete with multiple studies of diverse organisms, a few of which served as foundations for several fields, most were not pursued, abandoned largely for technical reasons that are no longer limiting. The time has come to revisit the old literature and to resurrect the organisms that are buried there, both to uncover new mechanisms and to marvel at the richness of the cellular world.